Pengaruh Sistem Informasi Sumber Daya Manusia dan Motivasi Kerja terhadap Kinerja pada Karyawan CV. Tirta Bening AMDK Kabupaten Cianjur - Wala Erpurini (LP2M Universitas Perjuangan Tasikmalaya, 2019)
This research aims to determine the information system of human resources, work motivation and performance, and to determine the magnitude of the influence of human resource information systems and work motivation both partially and simultaneously on the performance of employees. CV Tirta Bening AMDK Cianjur Regency. This research uses descriptive methods and associative methods. The unit of observation of this research is all permanent employees of CV. Tirta Benk AMDK. The sample takes 100% of the population in the CV. Tirta Bening AMDK of Cianjur Regency is as many as 35 respondents, taken from all permanent employees. To see the relationship between 2 variables, the analysis used is path analysis. This study resulted in the influence of the human resource information system on performance partially by 53.1%. The effect of work motivation on performance partially is 30.6%, so work motivation has a significant effect on performance. The influence of the human resource information system and work motivation simultaneous of 83.9% has a significant effect on performance.